1975
DOI: 10.1109/tap.1975.1141059
|View full text |Cite
|
Sign up to set email alerts
|

Rain attenuation of millimeter waves at λ = 5.77, 3.3, and 2 mm

Abstract: This region contains wide and na,rrow streets with low and high buildings and is representative of the heavily built-up downtown areas of many large cities in the United St.ates.The dist.ribut,ion of d indicates that the a.vera,ge error experienced by a CW ranging system would be >600 m over 10 percent. of t,he region. As an example of communications system limitations implied by the dist.ribut.ion of s, the bit rate for digital transmission cannot exceed 3012 bits!s if the irreducible error rate is to remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…However, several other models for the DSD have been reported in the literature (e.g., [13,49,50]), and efforts have been made to understand the feasibility of the gamma distribution in modeling the observed drop size spectra (e.g., [21,37,51]). Sekine and Lind [49] fitted the Weibull distribution to measured size spectra collected in Berlin [46] and Washington D.C. [32]. They found that the Weibull fit has a better performance than the exponential distribution, particularly for small diameters (<1 or 2 mm) and high rain rate (>25 mm h −1 ), because of the raindrop break-up.…”
Section: Introductionmentioning
confidence: 99%
“…However, several other models for the DSD have been reported in the literature (e.g., [13,49,50]), and efforts have been made to understand the feasibility of the gamma distribution in modeling the observed drop size spectra (e.g., [21,37,51]). Sekine and Lind [49] fitted the Weibull distribution to measured size spectra collected in Berlin [46] and Washington D.C. [32]. They found that the Weibull fit has a better performance than the exponential distribution, particularly for small diameters (<1 or 2 mm) and high rain rate (>25 mm h −1 ), because of the raindrop break-up.…”
Section: Introductionmentioning
confidence: 99%
“…The rain attenuation A in dB/Km is calculated by integrating over all of the drop sizes as A = 4.343 Q(D ,k,m)N(D)dD (5) where Q is the attenuation cross section which is a function of the drop diameter, D, the wavelength of the radio wave X and the complex refractive index of the water drop m which is a function of the frequency and the temperature, and N(D) is the drop-size distribution. The attenuation cross section Q is found by applying the classical scattering theory of Mie for a plane wave radiation to an absorbing sphere particle.…”
Section: Calculations Of Rain Attenuationmentioning
confidence: 99%
“…on surface rain using the flour pellet method, currently it is recommended to use the Laws and Parsons data for rain attenuation and scattering calculations [4]. However, the Laws and Parsons distribution was determined only for drops D > 1 mm so that the behaviour of the distribution is incorrect for very small drops less than D = 1 mm that still contribute a major part of the rain attenuation in millimeter and submillimeter ranges-In 1972, Sander [5] measured the size distribution of raindrops in Berlin by means of the electrostatilc method and the results were quite similar to the Laws and Parsons data.…”
Section: Introductionmentioning
confidence: 99%
“…Only simple tests on terrestrial and balloon-based links [11] [12], and some other proposals for future missions (the US. 3-GEO SWANsat constellation, and the Japanese 3-inclined GEO Quasi-Zenith satellite constellation) have been performed.…”
Section: Introductionmentioning
confidence: 99%